Effects of sulfamethoxazole-trimethoprim associated to resveratrol on its free form and complexed with 2-hydroxypropyl-β-cyclodextrin on cytokines levels of mice infected by Toxoplasma gondii - Bottari N.B. (2015)
© 2015 Elsevier Ltd.The aim of this study was to investigate the effects of resveratrol on its free form and complexed with 2-hydroxypropyl-β-cyclodextrin (HPβCD) when associated with sulfamethoxazole-trimethoprim (ST) on cytokines levels of mice (n=60) experimentally infected by Toxoplasma gondii. Groups A and E were used as controls (untreated): negative and positive, respectively. The onset of treatment started 20 days post-infection (PI), and it lasted for 10 consecutive days. ST was administered orally in doses of 0.5mgkg-1 for groups B and F, while 100mgkg-1 was the dose for resveratrol in its free form (groups C - G), inclusion complex (groups D and H), and on free and inclusion complex together (groups I - J). On day 31 PI, blood samples were collected in order to evaluate the cytokine profile. The mice that received drug combination (I and J) showed a significant (P<0.05) reduction in the number of cysts in the brain compared to other infected groups (E - H). The results showed that mice from the Group E had increased (P<0.001) levels of pro-inflammatory cytokines, while IL-10 levels were reduced when compared to the Group A. Additionally, there were increased levels of IL-4 and IFN-γ in animals of groups C and D, respectively (P<0.05). Animals of the Group B showed reduced levels of IL-1, IL-4, IL-6, TNF-α, and IFN-γ (P<0.05). Mice infected and treated (groups F - J) showed increased levels of pro-inflammatory cytokines along with a reduction of IL-10. Treatment with the combination of drugs (the Group J) led to a protective effect, i.e. reduction in pro-inflammatory cytokines. Therefore, resveratrol associated with ST was able to modulate seric cytokine profile and moderate the tissue inflammatory process caused by T.gondii infection, as well as to reduce parasite multiplication.